“My Sister Is the One That Made Me Stay Above Water”: How Social Supports Are Maintained and Strained When Survivors of Intimate Partner Violence Reside in Emergency Shelter Programs - Stylianou, Amanda M. (Journal of interpersonal violence, 2021)
While social support is critical in helping intimate partner violence (IPV) survivors heal and build hope, social isolation is a frequent experience for survivors. For survivors residing in domestic violence (DV) emergency shelters, the isolation from social supports is often exacerbated by shelter rules and policies. This study uses a 20th century feminist framework to understand the ways in which social support networks are maintained and/or strained when survivors reside in DV emergency shelters. Among this sample of 76 survivors, 40 participants identified family members as their support system, with siblings and mothers most frequently identified, and 14 participants identified friends as their social support. Prior to entering the DV shelter, survivors reported that their support networks provided encouragement and motivation along with emotional support, financial and material support, and support with children. Participants spoke about the process of informing their support systems of the transition into a DV shelter, the positive and negative impacts of the transition on their support system, and the roles that frequent telephone calls and texts played in maintaining their support networks. Participants reported positive impacts of residing in a DV shelter including improved emotional and physical health, strengthened emotional relationships, and improved physical and emotional resource provision. For those participants reporting negative experiences, they frequently identified logistical barriers, including the inability to receive visitors at the shelter, the distance between them and their friends and family, and strict rules around curfew and child care. Our findings invite researchers and practitioners to consider further examination of best practices around programming that supports survivors in maintaining social supports while residing in shelter programs